2015
DOI: 10.3758/s13423-015-0818-3
|View full text |Cite
|
Sign up to set email alerts
|

Action video games and improved attentional control: Disentangling selection- and response-based processes

Abstract: Research has demonstrated that experience with action video games is associated with improvements in a host of cognitive tasks. Evidence from paradigms that assess aspects of attention has suggested that action video game players (AVGPs) possess greater control over the allocation of attentional resources than do non-video-game players (NVGPs). Using a compound search task that teased apart selectionand response-based processes (Duncan, 1985), we required participants to perform an oculomotor capture task in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…Chisholm and Kingstone [118,119] showed a marginal effect in saccade latencies (with AVG players faster than NAVG players) during a cued visual search task (but see [98,118,120]). West et al [98] found greater attentional allocation to the cued target location in AVG players compared to NAVG ones.…”
Section: Visual Spatial Attention In Dyslexia and Action Video Gamesmentioning
confidence: 99%
“…Chisholm and Kingstone [118,119] showed a marginal effect in saccade latencies (with AVG players faster than NAVG players) during a cued visual search task (but see [98,118,120]). West et al [98] found greater attentional allocation to the cued target location in AVG players compared to NAVG ones.…”
Section: Visual Spatial Attention In Dyslexia and Action Video Gamesmentioning
confidence: 99%
“…AVGPs have been shown to possess larger attentional resources and display more flexibility in how they distribute these resources over space, time or to objects, which allows them to adapt to task demands (for reviews see Green & Bavelier, ; Spence & Feng, ). Eye‐tracking studies provide a convergent view by documenting initial oculomotor capture effects that are similar in AVGPs and NVGPs, but swifter recovery in AVGPS when wrongly cued (Chisholm, Hickey, Theeuwes, & Kingstone, ; Chisholm & Kingstone, , ). Search studies using manual reaction times, detection rate or eye‐tracking concur to demonstrate that AVGPS outperform NVGPs in detecting targets among distractors with some studies directly documenting fewer attention shifts (saccades) to task‐irrelevant distractors (Castel, Pratt, & Drummond, ; Chisholm & Kingstone, , , ; Clark, Fleck, & Mitroff, ; Hubert‐Wallander, Green, Sugarman, & Bavelier, ; Mack, Wiesmann, & Ilg, ; but see for another view Heimler, Pavani, Donk, & van Zoest, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is promising evidence that video game experience results in general improvement in attentional control, which, in turn, can be applied to various cognitive tasks (for a review, see Hubert‐Wallander, Green, & Bavelier, ). For example, Chisholm and Kingstone () found that action VGP outperform NVGP in selection‐based as well as response‐based processes of an oculomotor capture task indicating that experienced gamers benefit from enhanced attentional control. Advantages for action VGP in various attention‐demanding tasks have also been reported by Cardoso‐Leite et al.…”
Section: Introductionmentioning
confidence: 99%